Expression of matrix metalloproteinase-9 in acquired middle ear cholesteatoma - Vranješ, Dalibor; Spremo, Slobodan; Šolaja, Siniša (Biomedicinska istraživanja, 2020)
Introduction. Matrix metalloproteinase-9 (MMP-9) plays one of the key roles in the migration of inflammatory cells and the destructive behavior of acquired middle ear cholesteatoma. The aim of the study was to determine the expression levels of MMP-9 in chronic otitis media, with and without acquired cholesteatoma, as well as to determine the correlation between them and the pathomorphological changes in the tympanic membrane (TM). Methods. Immunohistochemical study included 178 patients of both sexes, aged 5-75 years, who underwent microsurgical treatment of chronic otitis media (COM) at the Ear, Nose and Throat Department of the University Clinical Center of the Republic of Srpska in Banja Luka from 2015 to 2018. Patients were divided into two groups on the basis of the presence or absence of acquired cholesteatoma: 97 (CCOM) and 81 (COMWC). The samples of the perimatrix of acquired cholesteatoma (n=97) and inflamed middle ear mucosa (n=81) were taken intraoperatively. The presence of retraction and certain types and subtypes of TM perforations were examined by intraoperative exploration. MMP-9 expression levels were determined by immunohistochemical analysis. Results. In the presence of cholesteatoma and highly positive expression of MMP-9, the marginal type of TM perforation was more likely to occur (p<0.01) while in negative expression of MMP-9 in the COMWC group, the central type was more likely to occur (p<0.01). There was a higher probability of the presence of attic subtype of TM perforation in patients with cholesteatoma and moderate positive expression of MMP-9 (p<0.01). There was not a statistically significant contribution of any of the factors in the prediction of the influence on the occurrence of TM retraction. Conclusion. The presence of acquired middle ear cholesteatoma and highly positive expression of MMP-9 are statistically significant predictors of the presence of marginal type and attic subtype of TM perforation. Expression levels of MMP-9 may have potential clinical significance in the development of irreversible pathomorphological changes on TM in middle ear cholesteatoma.